2019
DOI: 10.1016/j.cell.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Inhibition in Cell Specification Mediated by Mechanical Signals Modulating TAZ Activity

Abstract: Highlights d A single micropyle precursor cell (MPC) is specified within the granulosa cell layer d MPC specification relies on lateral inhibition of neighboring cells d Lateral inhibition is mediated by mechanical compression controlling nuclear TAZ d TAZ hyperactivation in MPC requires positive feedback from extracellular matrix

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…Numerous studies have reported that the PI3K/AKT pathway plays an important role in metastasis through the regulation of EMT [23][24][25]. Therefore, the PI3K inhibitor LY294002 [26][27][28][29] was used to detect the effect of the PI3K/AKT pathway on AGK-induced RCC proliferation and metastasis. As shown in Fig.…”
Section: Agk Promotes Rcc Proliferation and Metastasis Via The Pi3k/amentioning
confidence: 99%
“…Numerous studies have reported that the PI3K/AKT pathway plays an important role in metastasis through the regulation of EMT [23][24][25]. Therefore, the PI3K inhibitor LY294002 [26][27][28][29] was used to detect the effect of the PI3K/AKT pathway on AGK-induced RCC proliferation and metastasis. As shown in Fig.…”
Section: Agk Promotes Rcc Proliferation and Metastasis Via The Pi3k/amentioning
confidence: 99%
“…Such growth factor-mediated lateral inhibition can explain the salt-and-pepper distribution of cell types in the ICM (Chazaud et al, 2006;Rossant et al, 2003), although cell movement within the ICM likely precludes the observation of the canonical, alternate distribution of fates. Besides Delta-Notch signaling, lateral inhibition can also result from mechanical cues (Xia et al, 2019) and from secreted signaling molecules (Thompson et al, 2004). It has been proposed that high local concentrations of FGF4 may underlie this stochastic distribution of fates in the ICM of the blastocyst (Bessonnard et al, 2014;Kang et al, 2017;Tosenberger et al, 2017) and that the identity of neighbor cells affects fate choice (Fischer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such growth factor-mediated lateral inhibition can explain the salt-and-pepper distribution of cell types in the ICM (Chazaud et al, 2006;Rossant et al, 2003), although cell movement within the ICM likely precludes the observation of the canonical, alternate distribution of fates. Besides Delta-Notch signaling, lateral inhibition can also result from mechanical cues (Xia et al, 2019) and from secreted signaling molecules (Thompson et al, 2004). It has been proposed that high local concentrations of FGF4 may underlie this stochastic distribution of fates in the ICM of the blastocyst (Bessonnard et al, 2014;Kang et al, 2013;Tosenberger et al, 2017) and that the identity of neighbor cells affects fate choice (Fischer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%